2023
DOI: 10.21203/rs.3.rs-2610086/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delineation of Functional Changes and Associated Cortical Transcriptomic Profiles for Autism Spectrum Disorders

Abstract: Background: Although abnormal functional activities or connectivities in individuals with autism spectrum disorders (ASD) have been reported, yet, there is still lack of consistent findings of altered functional activities or connectivities and its associated genetic basis for ASD. Methods: Here, we aimed to identify consistent brain functional alterations and the biological genetic mechanisms in children and adults with ASD using a large sample of resting-state functional magnetic resonance imaging data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Regarding the statistical results of group differences between individuals with autism spectrum disorder (ASD) and healthy controls (HC), our research identified similar brain regions that have been highlighted in previous studies. For example, in patients with ASD, increased ALFF in the Temporal Lobe and Frontal Lobe while decreased ALFF in the Occipital Lobe was also found compared to HC (Wang et al, 2023). Participants with ASD also showed increased ReHo in the Frontal Lobe and decreased ReHo in the Temporal and Frontal Lobe compared to HC (Paakki et al, 2010;Canario et al, 2021;Wang et al, 2023).…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the statistical results of group differences between individuals with autism spectrum disorder (ASD) and healthy controls (HC), our research identified similar brain regions that have been highlighted in previous studies. For example, in patients with ASD, increased ALFF in the Temporal Lobe and Frontal Lobe while decreased ALFF in the Occipital Lobe was also found compared to HC (Wang et al, 2023). Participants with ASD also showed increased ReHo in the Frontal Lobe and decreased ReHo in the Temporal and Frontal Lobe compared to HC (Paakki et al, 2010;Canario et al, 2021;Wang et al, 2023).…”
Section: Figurementioning
confidence: 93%
“…For example, in patients with ASD, increased ALFF in the Temporal Lobe and Frontal Lobe while decreased ALFF in the Occipital Lobe was also found compared to HC (Wang et al, 2023). Participants with ASD also showed increased ReHo in the Frontal Lobe and decreased ReHo in the Temporal and Frontal Lobe compared to HC (Paakki et al, 2010;Canario et al, 2021;Wang et al, 2023).…”
Section: Figurementioning
confidence: 93%